Accuracy in Estimating Repetitions to Failure During Resistance Exercise. Issue 8 (August 2017) - Hackett, Daniel A.; Cobley, Stephen P.; Davies, Timothy B.; Michael, Scott W.; Halaki, Mark
Abstract : Abstract: Hackett, DA, Cobley, SP, Davies, TB, Michael, SW, and Halaki, M. Accuracy in estimating repetitions to failure during resistance exercise. J Strength Cond Res 31(8): 2162–2168, 2017—The primary aim of this study was to assess the accuracy in estimation of repetitions to failure (ERF) during resistance exercise. Furthermore, this investigation examined whether the accuracy in ERF was affected by training status, sex, or exercise type. Eighty-one adults (men, n = 53 and women, n = 28) with broad range of resistance training experience participated in this study. Subjects performed up to 10 sets of 10 repetitions at 70% 1 repetition maximum (1RM) and 80% 1RM for the chest press and leg press, respectively. At the completion of each set, subjects reported their ERF and then continued repetitions to failure to determine actual repetitions to failure (ARF). The accuracy (amount of error) of ERF was determined over an ARF 0–10. Significant differences were found for error of ERF among ARF ( p < 0.001), with the error of ERF ∼1 repetition at ARF 0–5 compared with >2 repetitions at ARF 7–10. Greater accuracy was found for the chest press compared with leg press, with the error of ERF ⩽1 repetition for ARF 0–5 and ARF 0–3, respectively ( p = 0.012). Men were found to be more accurate than women at specific ARFs for the leg press ( p = 0.008), whereas no interaction was found for the chest press. Resistance training experience did not affect the accuracy in ERF. These results suggest that resistance trainers can accurately estimate repetitions to failure when close to failure and that ERF could importantly be practically used for prescription and monitoring of resistance exercise.